Detection spread-out locality on pulse changing-state of bump-space stuff on hardened-skin - Kim, Jeong-Lae; Im, Yong-Soon; Lim, Yun-Sik; Song, Han-Chun; Kang, Geon-Uk (Edelweiss Applied Science and Technology, 2025)
Hardened skin on the foreign material, dark-hardened skin cells, is a broad variance that transports water drops like a superconductor in a single or multi-layer multi-block module. Reverberant categorization consciousness level (RCCL) within the hardened skin uses a technique of conveyance with a broad consciousness level function in the stiff spread-out convulsion status, mixing with pulse changes. In the spread-out convulsion status, the broad conveyance function within the hardened skin was calculated as the broad value found as a vector digital dot by the superstructure being observed. The broad convulsion function shown in the dermis layer consisted of a variance signal as a consciousness level based on the reverberant categorization level and was measured using the technical concept of pulse change of the diffusion convulsion function, converted to the value of RCCL by the maximum average. The degree of pulse change was expressed as the degree of water distribution within the hardened skin, and a value was formed according to the consciousness level of the convulsion function. In Bro-CL-FA-ΘMAX, the broad far variance value due to broad vector digital dot convulsion was shown as 16.19±2.4 units. In broad convenient variance value, Bro-CL-CO-ΘMAX was found to be 7.09±0.71. In broad flank variance value, Bro-CL-BRO-ΘMAX was found to be 2.43±0.49 units. In broad vicinage variance value, Bro-CL-VI-ΘMAX was found to be 0.45±0.05 units. In the dermis layer, spread-out convulsion by RCCL is evaluated by the degree of vector digital dot diffusion function shown at the broad consciousness level of bump-space material, and the dermis layer shown at the conveyance level system is expressed as a differentiated function and can be used. The function of the bump-space in the dermis layer is a concept that suppresses differential signals in diffusion consciousness systems and could be utilized as a promising key tool to utilize the data from a nanotechnology perspective and for basic applications for analyzing dark-hardened skin cells.